2010
DOI: 10.1510/icvts.2009.222778
|View full text |Cite
|
Sign up to set email alerts
|

Impact of number and site of lymph node invasion on survival of adenocarcinoma of esophagogastric junction☆

Abstract: Lymph node involvement in adenocarcinoma of the esophagogastric junction (EGJ) is similar to that of gastric cancer. The impact on survival of the number and site of lymph nodes involved in a subgroup of patients undergone surgery for adenocarcinoma of EGJ is reported. Sixty-four patients undergone transthoracic esophagectomy with two-field lymphadenectomy for adenocarcinoma of the EGJ were retrospectively assessed. Five-year survival according to AJCC gastric cancer nodal classification and central node invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…90-97) Key words: esophageal cancer, lymphatic vessel invasion, podoplanin, D2-40, lymph node metastasis, prognosis ageal cancer. More than 65% of patients with localized esophageal cancers and negative resection margin have a positive lymph node at the time of surgery [1]. However, despite complete tumor resection and extensive lymphadenectomy, systemic and local recurrence is common [2] and the five-year survival rate is 15-39% [3].…”
mentioning
confidence: 99%
“…90-97) Key words: esophageal cancer, lymphatic vessel invasion, podoplanin, D2-40, lymph node metastasis, prognosis ageal cancer. More than 65% of patients with localized esophageal cancers and negative resection margin have a positive lymph node at the time of surgery [1]. However, despite complete tumor resection and extensive lymphadenectomy, systemic and local recurrence is common [2] and the five-year survival rate is 15-39% [3].…”
mentioning
confidence: 99%
“…Fiveyear survival rates of T1 and T2 esophageal cancer patients are reported at 82% and 72%, respectively. 20 However, the five-year survival rate is 0 for patients with T3 or T4 disease. 20 Koufuji et al reported five-year survival rates of stage I, II, III, and IV of 86%, 40%, 21%, and 0, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the circumference of the AEG was manually drawn nodes. In the upper abdomen, nodes located along the cardia, lesser and large curvature, left gastric artery, celiac axis, common hepatic artery, and splenic artery were removed (16,17).…”
Section: Tumor Volume Measurementmentioning
confidence: 99%